Imidazole and Triazole Coordination Chemistry for Antifouling Coatings - Markus Andersson Trojer; Alireza Movahedi; Hans Blanck; Magnus Nydén (Journal of Chemistry)
Fouling of marine organisms on the hulls of ships is a severe problem for the shipping industry. Many antifouling agents are based on five-membered nitrogen heterocyclic compounds, in particular imidazoles and triazoles. Moreover, imidazole and triazoles are strong ligands for Cu2+ and Cu+, which are both potent antifouling agents. In this review, we summarize a decade of work within our groups concerning imidazole and triazole coordination chemistry for antifouling applications with a particular focus on the very potent antifouling agent medetomidine. The entry starts by providing a detailed theoretical description of the azole-metal coordination chemistry. Some attention will be given to ways to functionalize polymers with azole ligands. Then, the effect of metal coordination in azole-containing polymers with respect to material properties will be discussed. Our work concerning the controlled release of antifouling agents, in particular medetomidine, using azole coordination chemistry will be reviewed. Finally, an outlook will be given describing the potential for tailoring the azole ligand chemistry in polymers with respect to Cu2+ adsorption and Cu2+→Cu+ reduction for antifouling coatings without added biocides.